Auditors Response towards Auditing of Fair Value Measurement based Financial Reporting - Roekhudin Roekhudin (The Indonesian Journal of Accounting Research, 2018)
Abstract: The purpose of this study is to investigate the response of auditors of large and small accounting firms for the implementation of fair value as the basis of financial statements preparation. The researcher successfully interviewed five auditors from a large accounting firm and two accountants from small accounting firm. This study has found that both auditors from large or small accounting firms argue that auditing fair value financial reports is more difficult and at higher risk when compared to auditing financial statements based on historical cost. Furthermore, in addressing these conditions, auditors from small accounting firm are not interested in auditing the fair value financial report and prefer to accept clients who do not apply fair value. On the other hand, the auditor of the large accounting firm continues to receive the auditing of fair value financial reporting. However, as compensation for increases in audit difficulty and risk, they increase audit costs. As an additional finding, especially from the aspect of legal liability, the risk of auditing assignments viewed by auditors is more daunting than audit risk. That is, the auditor is afraid of punishment as stipulated in Law No. 5 of 2011 than the failed audit. Abstrak: Tujuan dari penelitian ini adalah untuk menyelidiki respon auditor dari perusahaan akuntansi besar dan kecil untuk pelaksanaan nilai wajar sebagai dasar penyusunan laporan keuangan. Peneliti berhasil mewawancarai lima auditor dari sebuah kantor akuntan besar dan dua akuntan dari kantor akuntan kecil. Studi ini telah menemukan bahwa kedua auditor dari perusahaan akuntansi besar atau kecil berpendapat bahwa mengaudit laporan keuangan nilai wajar lebih sulit dan berisiko lebih tinggi bila dibandingkan dengan mengaudit laporan keuangan berdasarkan biaya historis. Selanjutnya, dalam mengatasi kondisi ini, auditor dari kantor akuntan kecil tidak tertarik untuk mengaudit laporan keuangan nilai wajar dan lebih memilih untuk menerima klien yang tidak menerapkan nilai wajar. Di sisi lain, auditor dari perusahaan akuntan besar terus menerima audit pelaporan keuangan nilai wajar. Namun, sebagai kompensasi untuk peningkatan kesulitan dan risiko audit, mereka meningkatkan biaya audit. Sebagai temuan tambahan, terutama dari aspek tanggung jawab hukum, risiko pengauditan tugas yang dilihat oleh auditor lebih menakutkan daripada risiko audit. Artinya, auditor takut akan hukuman sebagaimana diatur dalam UU Nomor 5 tahun 2011 daripada audit yang gagal.